Pulmonary Effects of Neonatal Hydrocortisone Treatment in Ventilator-Dependent Preterm Infants - Sandra E. A. de Jong; Floris Groenendaal; Frank van Bel; Karin J. Rademaker (Hindawi Limited, 2011)
Background/Objective. Hydrocortisone, administered to ventilated preterm neonates to facilitate extubation, has no adverse long-term effects, but short-term pulmonary effects have not been described previously. In the present study, we analyzed effects of hydrocortisone on ventilator settings and FiO2 in ventilator-dependent preterm infants. Patients and Methods. Fifty-five preterm children were included in this retrospective cohort study. Hydrocortisone was administered at a postnatal age of > 7 days to treat chronic lung disease (CLD). Ventilator settings before and after hydrocortisone administration were recorded as well as FiO2 at 36 weeks' gestational age. Presence of cerebral palsy was assessed at a mean corrected age of 24.1 months. Results. Hydrocortisone administered at a median postnatal age of 14 days significantly reduced FiO2 from a median of 0.39 to 0.30, mean airway pressure (MAP) from a median of 10.0 cm H2O to 7.6 cm H2O, and PaCO2 from a median of 53.5 mmHg to 47 mmHg. Extubation was achieved in all patients. CLD at 36 weeks was present in 11 of the 52 patients (21.1%). None developed cerebral palsy. Conclusions. Hydrocortisone was effective in reducing the FiO2, MAP, and PaCO2 and facilitated extubation. Hydrocortisone was not associated with cerebral palsy.